How Changes in Reimbursement Practices Influence the Financial Sustainability of Medicine Policy: Lessons Learned from Slovakia - Tesar, Tomas; Obsitnik, Branislav; Kaló, Zoltán; Kristensen, Finn Børlum (Frontiers in Pharmacology, 2019)
Objectives: The aim of this study was to review the impact of new reimbursement requirements for medicines in the Slovak Republic based on legislation that came into force in January 2018. Methods: The new legislation was reviewed. The reimbursement dossiers for medicines and health technology assessments and appraisals, justifications for reimbursement decisions, final reimbursement decisions, and all aspects of the appeal mechanisms have been transparently published on the website of the Slovak Ministry of Health and were used for this analysis. Results: Based on the new legislation, there was no need to submit information about relative effectiveness and cost-effectiveness of medicines with less than 1:50,000 eligible patients prior to reimbursement decisions, and the cost-effectiveness threshold has been increased for all other medicines. The estimated impact of the 2-year budget for the 59 medicines submitted for reimbursement without relative effectiveness and cost-effectiveness analysis was €181,273,698, based on the published submission dossiers. The estimated impact of the 2-year budget for the 45 medicines with evidence of relative effectiveness and cost-effectiveness was €178,566,634. In contrast to the easier market access criteria for new original medicines, the new legislation enforces stricter price erosion criteria for generic and biosimilar medicines. Consequently, the number of generic and biosimilar entries was reduced from 242 in 2017 to 224 in 2018. Conclusions: Although some of the new reimbursement applications were not approved by the Ministry of Health, many new medicines were added to the Slovak pharmaceutical reimbursement list based on ‘balanced assessment’ requirements; hence, the system became financially unsustainable. It was necessary to change the legislation from January 2019.